Phosphate fertilizers containing plant growth promoters - Cuesta, Rafael Lucas Coca (2021)
Plant growth promoters (PGPs) are substances with actions in plants that are analogous to plant hormones belonging to the auxin, cytokine, and gibberellin groups.These substances have great potential for use in agriculture because they can contribute to increasing the efficiency of water and nutrient absorption, by stimulating root development and increasing the photosynthetic rate, through the vegetative growth of plants. The association of PGPs and phosphate fertilizers is an efficient and practical way of using these substances, which is viable through the granulation process of the compounds using the sodium alginate polymer. Therefore, the objectives of this work were to produce phosphate fertilizers containing PGPs and to evaluate the efficiency in promoting the growth of the roots and aerial parts, and increase the absorption of P by the plants. The available fertilizers contained reactive natural phosphate and PGPs idol-3-butyric acid (PR_IBA), humic substance (PR_HS), or Trichoderma afroharzianum (PR_TA). In addition, a control fertilizer (PR_CONTROL) was produced without PGPs. To evaluate the efficiency of fertilizers in promoting plant growth, a trial was carried out in a factorial scheme [(3 + 1 + 1) × 2], with three fertilizers containing PGPs (PR_IBA, PR_HS, and PR_TA), a control fertilizer, without PGPs (PR_CONTROL), and an additional treatment, with the monoammonic phosphate fertilizer (MAP) and two contrasting soils (clayey and sandy soil). The treatments were distributed in a randomized block design, with five replications. The experimental unit consisted of a rhizobox containing 350 cm3 of soil, where a soybean plant (‘BMX Ipro 8579’) was grown. After thirty days of growth, the root length, average root diameter, root tips, and fine roots were measured using WinRHIZO software. In addition, the dry matter mass and P content of the roots and shoots were determined. The data obtained were subjected to analysis of variance and test of means by the Scott Knott test (p < 0.05). Plant growth promoters have a great potential to increase phosphorus use efficiency. The effects of PGPs were observed in the architecture of the root system, leaf area, and increased P content by plants. The efficiency of plant growth promoters in phosphate rock increases in the following order: humic substances > Trichoderma afroharzianum > indole-3-butyric acid.